Recyclable amitraz-ethylene vinyl acetate strips used for beehives treatment against Varroa destructor. (August 2018) - Karp, Federico; Luna, Julio A; Mengatto, Luciano N
In this work, a new recyclable ethylene-vinyl acetate (EVA)-based strip impregnated with amitraz (AMZ) was prepared, characterized, and evaluated for the treatment of Apis mellifera against Varroa destructor . Bees are important for natural pollination, honey, and related goods production. Varroa destructor is currently considered one of the major pests and important efforts around the world are focused on methods for varroasis treatment. The procedure of strips preparation presented in this work consisted of two steps: impregnation and molding of impregnated pellets. Differential scanning calorimetry and gas chromatography–mass spectrometry analyses confirmed that AMZ molecule resisted the impregnation and molding conditions. The strips were sufficiently strong to resist destruction by the bees. The final infestation was lower in the hives treated with AMZ/EVA strips than in those treated with commercial strips. In order to check the possibility of recycling, strips were cut into little pieces and were subjected to total AMZ extraction. Finally, the fragments were exposed to re-impregnation and molding. The strips prepared after the recycling process presented the same shape and AMZ load than fresh strips.